Pengaruh Intensitas Komunikasi Interpersonal Dan Motivasi Belajar Terhadap Prestasi Belajar Siswa SD IT Aisyah Fullday Pandes - Dwi Prasetyo, Alfian, Dr. Ahmad Muhibbin, M. Si (2017)
ABSTRACT This research aims to know the influence of intensity of interpersonal communication and motivation towards learning learning achievements of students IT Aisha FullDay Pandes. This research uses a quantitative approach, using the quota sampling purposive random sampling proportional to the number of samples as many as 30 students. The validity of the data by correlation product moment rough figures, while for reliability with the use of side two. Data analysis techniques used in this research are multiple linear regression test. The results showed a variable intensity of interpersonal communication effect on student learning achievement of 0,004 < 0.05. Learning motivation variables affect student learning achievement represented by the value of 0.000 < 0.05. Test results showed the simultaneous variable intensity of interpersonal communication and motivation learn effect significantly to student learning achievement demonstrated by the significant value of 0,000 < 0,05. The contribution of a given variable intensity of interpersonal communication and learning motivation of 97.3% 2.7% influenced by variables other than this research. Keywords: Intensity Of Interpersonal Communication, Learning, Learning Achievement Motivation